Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for the Treatment of Adults With Metastatic Brain Tumors: Executive Summary. Issue 3 (9th January 2019) - Olson, Jeffrey J; Kalkanis, Steven N; Ryken, Timothy C
Abstract: BACKGROUND: The Congress of Neurological Surgeons systematic review and evidence-based clinical practice parameter guidelines for the treatment of adults with metastatic brain tumors was first published in 2010. Because of the time elapsed since that publication, an update of this set of guidelines based on literature published since is now indicated. OBJECTIVE: To establish the best evidence-based management of metastatic brain tumors over all commonly used diagnostic and treatment modalities in regularly encountered clinical situations. METHODS: Literature searches regarding management of metastatic brain tumors with whole brain radiation therapy, surgery, stereotactic radiosurgery, chemotherapy, prophylactic anticonvulsants, steroids, instances of multiple brain metastases, and emerging and investigational therapies were carried out to answer questions designed by consensus of a multidisciplinary writing group. RESULTS: Recommendations were created and their strength linked to the quality of the literature data available thus creating an evidence-based guideline. Importantly, shortcomings and biases to the literature data are brought out so as to provide guidance for future investigation and improvements in the management of patients with metastatic brain tumors. CONCLUSION: This series of guidelines was constructed to assess the most current and clinically relevant evidence for management of metastatic brain tumors. They set a benchmark regarding the current evidence base for this management while also highlighting important key areas for future basic and clinical research, particularly on those topics for which no recommendations could be formulated. The full guideline can be found at: https://www.cns.org/guidelines-treatment-adults-metastatic-brain-tumors/chapter_1 .